Antibacterial mechanism of plantaricin LPL-1, a novel class IIa bacteriocin against Listeria monocytogenes. (March 2019) - Wang, Yao; Qin, Yuxuan; Zhang, Ying; Wu, Ruiyun; Li, Pinglan
Abstract: Plantaricin LPL-1, produced by Lactobacillus plantarum LPL-1, is a novel class IIa bacteriocin with bactericidal activity against foodborne bacteria. The aim of this present study was to understand the antibacterial activity and mechanism of plantaricin LPL-1 against Listeria monocytogenes 54002, one of the Gram-positive bacteria sensitive to this bacteriocin and typical foodborne pathogenic bacteria in the food industry. The minimal inhibitory concentration (MIC) was confirmed as 16 μg/mL, and the time-kill kinetics showed that plantaricin LPL-1 significantly decrease the viable cell numbers of L. monocytogenes 54002 in a time-dependent and dose-dependent manner. The antibacterial mechanism was investigated using confocal laser-scanning microscopy, scanning and transmission electron microscopy, spectrofluorimeter, spectrophotometer and Real-Time PCR system, which demonstrated that plantaricin LPL-1 facilitated pores formation, damaged cell membrane integrity, increased membrane permeability, triggered intracellular material leakage, induced collapse of proton motive force, and inhibited expression levels of genes related to virulence factors, biofilm formation factors, and RNA polymerase sigma factor. Hence, the bactericidal mechanism of plantaricin LPL-1 against L. monocytogenes was clarified at cellular and molecular levels. Highlights: Plantaricin LPL-1 damaged cell membrane integrity, permeability and proton motive force. Plantaricin LPL-1 inhibited expression levels of virulence, biofilm formation, and RNA polymerase genes. The hypothetical antibacterial mechanism was described.